Study of Manganese-1, 4-Benzenedicarboxylate Metal Organic Framework Electrodes Based Solid State Symmetrical Supercapacitor. (February 2019) - Sundriyal, Shashank; Mishra, Sunita; Deep, Akash
Abstract: In this work, manganese MOF is synthesized using one step solvothermal method and utilized as an electrode for supercapacitor applications. The high specific surface area, chemical & thermal stability and pseudocapacitive charge storage mechanism of Mn-BDC MOF facilitates fast electronic and ionic transport. When the Mn-BDC MOF is tested as an electrode for supercapacitor applications, the electrode exhibits remarkable electrochemical performance using 1 M Na2 SO4 aqueous electrolyte. The Mn-BDC electrode shows a highest specific capacitance of 177.9 F/g at a current density of 0.5 A/g and 166.4 F/g at a scan rate of 1 mV/s. Further, an all-solid-state symmetrical supercapacitor is assembled using two equally weighted Mn MOF electrodes using PVA-1 M Na2 SO4 polymer gel electrolyte. The solid state symmetrical supercapacitor device shows a highest specific capacitance of 64.5 F/g at a current density of 0.25 A/g within an operating potential window of 0-1.5 V. Also, the device delivers an energy density and power density of 4.3 Wh/kg and 171.6 W/kg respectively along with a very high capacity retention of 98 % even after 2000 charge-discharge cycles. Therefore, the excellent electrochemical performance of Mn MOF electrodes and symmetrical device proves its superiority for practical supercapacitor applications.